PENGARUH INFLASI, PRODUK DOMESTIK REGIONAL BRUTO DAN INVESTASI TERHADAP PENGANGGURAN TERDIDIK DI KOTA LHOKSEMAWE TAHUN 2008-2022 - Rahmah, Mutia; Musdalipah, Musdalipah; Juliansyah, Hijri; Syafira, Syarifah (LPPM UNIMAL, 2024)
The aim of this research is to analyze the influence of Inflation, Gross Regional Domestic Product (GRDP) and Investment on Educated Unemployment in Lhokseumawe City. The data used in this research is secondary data obtained from publications by the Central Statistics Agency (BPS) and the Medium Term Development Plan (RPJM) of Lhokseumawe City for 15 years (2008-2022). This research uses the Multiple Linear Regression analysis method using Eviews. The results of this research show that inflation has a positive effect on educated unemployment in the city of Lhokseumawe. Gross Regional Domestic Product (GRDP) has no effect on educated unemployment in the city of Lhokseumawe. And investment has a positive effect on educated unemployment in the city of Lhokseumawe. Based on the results of tests carried out simultaneously on inflation, Gross Regional Domestic Product (GRDP) and investment have a significant effect on educated unemployment in Lhokseumawe City.